The autocracy of meaning: Intact visuo-imitative processes may not compensate for meaningful gestures. (May 2021) - Mauri, Ilaria; Zanin, Valeria; Aggujaro, Silvia; Molteni, Franco; Luzzatti, Claudio
Abstract: The dual-route models of action distinguish between a semantic and a non-semantic visuo-motor route to execute different types of gestures. Despite the large amount of evidence in support to the model, some aspects are debated. One issue concerns the recruitment of the visuo-motor route to correctly execute meaningful gestures when the semantic route is damaged. Debated predictions of the dual-route model were investigated in a sample of 32 patients with left hemisphere stroke lesions compared to 27 healthy controls. Group analysis showed that patients were equally impaired on meaningful and meaningless gestures. Single-case analysis demonstrated that most cases were more impaired on meaningful than on meaningless gestures both when they are given in separate lists and when they are intermingled. Impaired performance on the imitation of meaningful gestures in both the separate and mixed list but spared performance on meaningless gestures in the separate list is against the hypothesis that the intact visuo-motor route compensates for damage to the semantic route. These results suggest that the damaged semantic route interferes with the visuo-motor route and prevents the processing of meaningful gestures along the visuo-motor route. Furthermore, an explorative analysis was conducted to investigate the relationship between gestures imitation and pantomime of object use on verbal command and between gestures imitation and performance on linguistic tasks. Although no significant correlation emerged, patients with moderate/severe impairment on the AAT performed significantly worse on meaningful, but not on meaningless gestures than patients with mild/minimal language impairment, suggesting that praxis and language systems are independent but dynamically interact.